Cadangan Karbon pada “Kabun” di Kabupaten Katingan Kalimantan Tengah - Nanang Hanafi; Ise Afitah; Jariah Jariah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Kabun is a traditional farming system commonly practiced by people in Katingan District, Central Kalimantan. Land management carried out by the people of Katingan District since long ago using shifting cultivation. This farming system is an agroforestry system. The existence of "kabun" is expected as one of the mitigations of climate change, by maintaining the vegetation in the "kabun." The purpose of this study is to predict carbon storage of "kabun" as well as the history of management in the Buntut Bali Village, Pulau Malan subdistrict, Katingan District, Central Kalimantan. This research was carried out destructively for understorey and litter, and nondestructive for tree biomass and woody necromasses were carried out in 3 observation plots. In the observation plot 1 was obtained carbon stocks of 88.915 tons/ha, the presence of tree biomass contributed to carbon reserves of 81.263 tons/ha; plot of observations of the 2 carbon stocks obtained was 66,928 tons / ha, the most significant contribution of carbon stocks came from tree biomass 61,209 tons/ha; The plot of observations of the 3 carbon stocks was obtained at 72,375 tons/ha, and the biomass contribution of trees was 65,643 tons / ha.